Protocol to refine intestinal motility test in mice - Marona, Hérida Regina Nunes [UNESP]; Lucchesi, Maria Beatriz Bastos [UNESP] (SAGE Publications, 2004)
We propose a new protocol intended to conform to the 3Rs (replacement, reduction, and refinement) principle, using animals fasted for 3 h to control intestinal motility, which reduced stress in the animals. In this new protocol, mice are deprived of food for a short time (3 h) and are not killed. The mice are observed until evacuation containing charcoal is observed, and the experimental results are based on the charcoal evacuation time. The present study may aid the formulation of recommendations that can be included in revised guidelines relating to the fasting time of mice. This new concept of an intestinal motility test conforms with respectful science.
Keywords: Animal welfare; In vivo test; Intestinal motility; Loperamide; charcoal; animal experiment; controlled study; diet restriction; female; intestine motility; intestine transit time; methodology; mouse; nonhuman; stress; time; Animal Use Alternatives; Animals; Animals, Laboratory; Charcoal; Fasting; Gastrointestinal Motility; Mice; Time Factors; Animalia